2008
DOI: 10.1002/jsfa.3339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L‐carnitine supplementation to diets with different fat sources and energy levels on fatty acid composition of egg yolk of laying hens

Abstract: BACKGROUND: The present study was carried out to determine the effects of feeding diets with two different levels of metabolisable energy (ME) (11.51 or 10.88 MJ ME kg −1 diet) and three different sources of fat (palm oil, sunflower oil or fish oil) with or without supplemental L-carnitine (0 or 500 mg kg −1 diet) on the fatty acid (FA) composition of egg yolk and the passage of n3 polyunsaturated FAs to egg yolk in laying hens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
3
1
0
Order By: Relevance
“…These results agreed with [14,15,22], as for the effect of carnitine levels, we observe that there are no significant differences in the characteristics of feed consumption rate, feed conversion efficiency, and ratio of deaths, where the treatment 200 mg/kg fodder was less feed consumption and better feed conversion efficiency. These results agreed with what was found by [18,20,24]. As for the effect of strain interaction with carnitine treatments, we find a significant superiority in the characteristics of feed conversion efficiency (gm/gm eggs) but the interaction of white quail with the treatment 250 mg /kg fodder was the lee value in feed conversion efficiency, which confirms that it was the best among the interactions in the efficiency of converting food into eggs.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These results agreed with [14,15,22], as for the effect of carnitine levels, we observe that there are no significant differences in the characteristics of feed consumption rate, feed conversion efficiency, and ratio of deaths, where the treatment 200 mg/kg fodder was less feed consumption and better feed conversion efficiency. These results agreed with what was found by [18,20,24]. As for the effect of strain interaction with carnitine treatments, we find a significant superiority in the characteristics of feed conversion efficiency (gm/gm eggs) but the interaction of white quail with the treatment 250 mg /kg fodder was the lee value in feed conversion efficiency, which confirms that it was the best among the interactions in the efficiency of converting food into eggs.…”
Section: Resultssupporting
confidence: 91%
“…80 mm. These results agreed with [24], as for the interaction between the strain and the feeding treatments on the levels of carnitine, we observe that there are significant differences (p≤0.05) between the interactions in the characteristics of albumen height and yolk diameter, where the interactions between the treatment of desert quail 250 mg carnitine /kg fodder were superior to the rest of interactions, where the height of the yolk was 6.41 mm, while the diameter of yolk was 24,53. The reason for this may be due to the cumulative effect of the outcome of heredity and nutrition.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the results of the present experiment, researchers reported that supplementation of fish oil in the diet significantly reduced the ratio of omega-6 to omega-3 fatty acids ( Garcia-Rebollar et al, 2008 ; Omidi et al, 2015 ). In one study, adding 500 mg/kg L-carnitine to the diet enhanced the beta-oxidation of mitochondrial long-chain fatty acids by facilitating their transmission across the inner mitochondrial membrane ( Corduk et al, 2008 ). Thus, L-carnitine can improve the body's utilization of energy and fatty acids ( Mast et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found by Rizk et al,(2022) found that adding L-carnitine (300 and 450 mg/kg food) to the broiler diet significantly increased (P≤0.05) egg laying compared to the control diet. However, Corduk and Sarica, (2008); Kazemi-Fard et al, (2015) concluded that dietary intake of 100 and 150 mg/kg L-carnitine increased egg production in laying hens by 7.81 and 10.74%, respectively, because this additive (L-carnitine) improves lipolysis and liver protection. Neuman et al, (2002) found that Lcarnitine supplementation increased mitochondrial energy production and in turn, laying intensity in these birds.…”
Section: Hen Day Egg Production (Hd%)mentioning
confidence: 99%